PELATIHAN PENINGKATAN KAPASITAS APARAT DESA TENTANG DIGITALISASI ADMINISTRASI PEMERINTAHAN DAN PEMBANGUNAN DESA SE-KECAMATAN RANOMEETO BARAT KABUPATEN KONAWE SELATAN - Sartono, Sartono; Qomatiyah, Erni; Liwaul, Liwaul; Hairani Idrus, Sitti; Elwan, La Ode Muhammad; Taufik, Taufik; Aslim, La Ode (Universitas Halu Oleo, 2024)
This paper aims to determine the implementation of Thematic KKN through Village Apparatus Capacity Building Training on Digitalization of Government Administration and Village Development throughout Ranomeeto Barat District, South Konawe Regency which began on July 24 to August 30, 2024. The method used through several stages, namely socialization, training, and evaluation of implementation. The results of the community service show that the implementation of UHO Thematic KKN in 2024 has been carried out well. However, in general, village government officials do not yet understand the importance of digitalization of government administration and village development.